2023
DOI: 10.1002/smll.202300751
|View full text |Cite
|
Sign up to set email alerts
|

Nanoheterostructure by Liquid Metal Sandwich‐Based Interfacial Galvanic Replacement for Cancer Targeted Theranostics

Abstract: Nanoheterostructures with exquisite interface and heterostructure design find numerous applications in catalysis, plasmonics, electronics, and biomedicine. In the current study, series core–shell metal or metal oxide‐based heterogeneous nanocomposite have been successfully fabricated by employing sandwiched liquid metal (LM) layer (i.e., LM oxide/LM/LM oxide) as interfacial galvanic replacement reaction environment. A self‐limiting thin oxide layer, which would naturally occur at the metal–air interface under … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 78 publications
1
3
0
Order By: Relevance
“…The extracted surface profile and the WLI image confirmed that some topography exists; however, the overall surface as shown using SEM presented a smooth surface. Overall, the electrode quality looked similar to that reported by Park et al [ 45 ]. On the contrary, the WO-Galinstan electrode had a thickness of 2.68 µm ± 0.8 µm, which is around 0.75 µm greater than the pristine Galinstan electrode, indicating that 24 h immersing in 400 mM W salt resulted in a WO layer with thickness of ~0.75 µm.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…The extracted surface profile and the WLI image confirmed that some topography exists; however, the overall surface as shown using SEM presented a smooth surface. Overall, the electrode quality looked similar to that reported by Park et al [ 45 ]. On the contrary, the WO-Galinstan electrode had a thickness of 2.68 µm ± 0.8 µm, which is around 0.75 µm greater than the pristine Galinstan electrode, indicating that 24 h immersing in 400 mM W salt resulted in a WO layer with thickness of ~0.75 µm.…”
Section: Resultssupporting
confidence: 86%
“…This potential difference results in the reduction of metal ions in a solution phase and their deposition on the sacrificial template [ 35 ]. In recent years, GR of gallium liquid metals with various metal ions in solution has been successfully shown to allow the generation of controllable nanostructured surfaces for noble and non-noble metals, such as gold, platinum, silver, and copper; semiconductors, such as manganese and molybdenum oxide; and core-shell metal/metal oxides, such as WOx and VOx [ 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. This mainly stems from the negative standard reduction potentials of −0.529 V (Ga 3+ /Ga 0 ), −0.340 V (In 3+ /In 0 ), and −0.138 V (Sn 2+ /Sn 0 ), which readily undergo GR reactions with metal ions possessing higher standard reduction potentials, e.g., 0.799 V (Ag + /Ag 0 ) [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…To enhance the antitumor efficacy, photothermal/photodynamic therapy could be integrated in the treatment process due to the photothermal effect of liquid metal . In addition, the photothermal effect of MRLM microparticles after magnetically targeted accumulation can generate spatiotemporally enhanced temperature contrast, which can be used for photothermal imaging to evaluate antitumor therapy …”
Section: Applications For Magnetically Responsive Liquid Metalmentioning
confidence: 99%
“…[ 12 ] These structures combine the synergistic properties of the LM core and solid metal NP shell, enabling diverse applications such as photocatalysis, [ 13 ] self‐healing flexible circuits, [ 14 ] photothermal therapy, [ 15 ] and magnetic resonance imaging. [ 16 ] However, the conventional core–shell structures generated through galvanic replacement have random NP shells with uncertain size distribution and morphology. [ 17 ] This lack of control hinders the understanding of how to precisely tune the properties of core–shell nanostructures using galvanic replacement.…”
Section: Introductionmentioning
confidence: 99%